ANALISIS CROSS-SECTIONAL SIKAP KELUARGA BERDASARKAN PENINGKATAN PENGETAHUAN DALAM MERAWAT LANSIA STROKE - Sarah Fitria; Chandra Tri Wahyudi (Jurnal Ilmiah Keperawatan IMELDA, 2026)
Stroke in older adults often causes physical, cognitive, and emotional limitations that require long-term care at home. In this condition, the family acts as the primary caregiver, making family knowledge and attitudes important factors in the success of caring for older adults with Stroke. Although many studies have discussed the role of families in Stroke care, most focus on caregiver burden or patient quality of life, while studies examining the relationship between family knowledge and attitudes in caring for older adults with Stroke in the community remain limited. This study aimed to analyze the relationship between the level of knowledge and family attitudes in caring for older adults with Stroke in Limo District, Depok City. This study used a quantitative analytic design with a cross-sectional approach. The sample consisted of 124 families caring for older adults with Stroke, selected using a total sampling technique. Data were collected using the Stroke Knowledge Assessment Tool (SKAT) questionnaire to measure knowledge and the Family Caregiver Patient Stroke questionnaire to assess family attitudes. Data were analyzed using the Chi-Square test. The results showed that most families had low knowledge levels and negative attitudes toward caring for older adults with Stroke. Bivariate analysis showed a significant relationship between knowledge level and family attitudes (p < 0.001). These findings indicate that family knowledge plays an important role in shaping attitudes toward caring for older adults with Stroke at home.